Determinan manajemen laba dan nilai perusahaan - Karnawati, Yosevin; Handayani, Sri; Abdurrahman, Abdurrahman; Wahyuningsih, Dwi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
Earnings management is still often carried out by companies with the aim of increasing firm value. The purpose of this research is to see the effect of good corporate governance and audit quality on earnings management and firm value. The sample is 77 food and beverage industry sub-sectors listed on the IDX for the 2017-2019 period using a purposive sampling technique. Two-stage least square is used as a research method, to see the effect of good corporate governance and audit quality on earnings management and firm value. The results showed that simultaneously good corporate governance and audit quality had an effect on earnings management and firm value. Partial testing shows that the audit committee and independent commissioners have a negative effect on earnings management and institutional ownership and independent commissioners have a positive effect on firm value, while earnings management has no effect on firm value. This proves that the existence of audit committees and independent commissioners can reduce earnings management, while institutional ownership and independent commissioners can increase firm value.